Analisis Kejadian Diare Pada Balita di Tatanan Rumah Tangga - Muharry, Andy; Amalia, Icca Stella; Dwihayati, Aat (Sekolah Tinggi Ilmu Kesehatan Kuningan, 2017)
Diarrhea is one of the diseases that can cause special death in children. The incidence of diarrhea in Karamatwangi Village is quite high compared to other villages. Diarrhea is generally associated with public health concerning clean and healthy living behavior in the household setting. The purpose of research factors related to the incidence of diarrhea in the household setting. This research use analytical approach with cross sectional design. The population is mother of toddler which is domiciled in Karamatwangi Village as many as 115. Samples were taken by simple random sampling as many as 55 toodler. The research instruments used questionnaires, interviews, and observations. Data analysis bivariable and multivariable The results of the analysis with chi-square found that the variables associated with diarrhea occurrence in infants in the household setting were exclusive breastfeeding (p = 0,034; OR =) use of clean water (p = 0,002; OR =), stove behavior with clean water and soap ( p = 0,000; OR =), use of healthy latrine (p = 0,005; OR =). The most severe factors for the occurrence of diarrhea in toodler are behavior with clean water and soap (p = 0,000; OR = 22,185) 95% CI 4,006-122,850 and the benefits of healthy latrine is a factor associated with the incidence of diarrhea in toddler. The most dominant factor with the incidence of diarrheain infants is hand relief using clean water and soap.